2020
DOI: 10.3389/fpls.2020.01150
|View full text |Cite
|
Sign up to set email alerts
|

Rice OsLHT1 Functions in Leaf-to-Panicle Nitrogen Allocation for Grain Yield and Quality

Abstract: Proper allocation of nitrogen (N) from source leaves to grains is essential step for high crop grain yield and N use efficiency. In rice ( Oryza sativa ) grown in flooding paddy field, amino acids are the major N compounds for N distribution and re-allocation. We have recently identified that Lysine-Histidine-type Transporter 1 ( OsLHT1 ) is the major transporter for root uptake and root-to-shoot allocation of amino acids in rice. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 71 publications
0
41
0
Order By: Relevance
“…Root importers for amino acids include amino acid permeases AAP1 and AAP5, proline transporter ProT2, and lysine-histidine-type transporters LHT1 and LHT6 (Grallath et al, 2005 ; Hirner et al, 2006 ; Lee et al, 2007 ; Svennerstam et al, 2007 , 2008 , 2011 ; Lehmann et al, 2011 ; Perchlik et al, 2014 ; Ganeteg et al, 2017 ; Wang et al, 2019 ; Guo et al, 2020a , b ), and their importance for plant growth has been demonstrated (Tegeder and Masclaux-Daubresse, 2018 ; Guo et al, 2020a ). In rice, constitutive overexpression of OsAAP1 led to increased N uptake and reallocation, positively affecting tiller number and final grain yield ( Figure 1 ; Ji et al, 2020 ).…”
Section: Importance Of Amino Acid Uptake and Root-to-shoot Allocationmentioning
confidence: 99%
“…Root importers for amino acids include amino acid permeases AAP1 and AAP5, proline transporter ProT2, and lysine-histidine-type transporters LHT1 and LHT6 (Grallath et al, 2005 ; Hirner et al, 2006 ; Lee et al, 2007 ; Svennerstam et al, 2007 , 2008 , 2011 ; Lehmann et al, 2011 ; Perchlik et al, 2014 ; Ganeteg et al, 2017 ; Wang et al, 2019 ; Guo et al, 2020a , b ), and their importance for plant growth has been demonstrated (Tegeder and Masclaux-Daubresse, 2018 ; Guo et al, 2020a ). In rice, constitutive overexpression of OsAAP1 led to increased N uptake and reallocation, positively affecting tiller number and final grain yield ( Figure 1 ; Ji et al, 2020 ).…”
Section: Importance Of Amino Acid Uptake and Root-to-shoot Allocationmentioning
confidence: 99%
“…AtUCP1 and AtUCP2 have sequence similarity of about 72%; however, they differ significantly in their specific activity, making AtUCP1 more active in the transport of Asp/Glu than AtUCP2 [51]. Additionally, a recent report shows that the knockout of lysine-histidine-type transporter 1 (OsLHT1) in rice affected root uptake of Asp, which eventually impaired the nitrogen translocation to the shoot, suggesting that OsLHT1 could possibly be an Asp transporter as well [55]. Despite several putative Asp membrane transporters identified to date in different genome databases, their transport capabilities in plants are yet to be investigated.…”
Section: Aspartate Transportersmentioning
confidence: 99%
“…Based on gene-based genetic association analysis of aspartate uptake between japonica and indica rice subspecies, Lysine-Histidine-type Transporter 1 (OsLHT1) was identified as a candidate gene [66]. OsLHT1 is expressed throughout the root and in the leaf, and oslht1 mutants showed the reduced amino acids root uptake and allocation from root to shoot, thereby growth inhibition and low yield [66][67][68]. Plasma membrane-localized OsProT1 and OsProT3 function to specifically mediate transport of Pro and GABA in yeast and showed differential expression patterns [69].…”
Section: Amino Acid Permeasesmentioning
confidence: 99%